The vertex form of the equation y=x^2+6x-9 can be found by completing the square.
First, we group the first two terms together and leave the constant term separate:
y = (x^2 + 6x) - 9
Next, we need to complete the square by adding and subtracting a constant, which is half the coefficient of the x term squared. In this case, that constant is (6/2)^2 = 9.
y = (x^2 + 6x + 9 - 9) - 9
We can rewrite the first three terms as a perfect square trinomial:
y = (x+3)^2 - 9 - 9
Finally, we combine the constant terms:
y = (x+3)^2 - 18
Therefore, the correct vertex form of the equation is y = (x+3)^2 - 18.
Select the correct vertex form of the following equation y=x2+6x-9
1 answer